The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.18203/2349-3291.ijcp20202625
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum sodium levels in recurrence and recurrent episodes of febrile seizure

Abstract: Background: Simple febrile seizures are the common childhood seizures, usually affecting 1 in 20 children between the age group of 6 months to 60 months. Earlier studies have shown an association between low serum sodium as a cause for febrile seizures and its recurrences. The present study was to determine the role of serum sodium in predicting febrile seizure recurrence within 24 hrs and recurrent episodes.Methods: Children aged between 6 months to 60 months with first episode of febrile seizures, admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…6,12 However, studies have been reported in contrast to this evidence, 15,16 and the role of relative hyponatremia instead of serum sodium levels in the predisposition of the child to simple febrile seizure has been speculated. 17,18 Lower levels of mean sodium levels have been reported in patients with repeat convulsions, which was comparable to our study. 6 Lower sodium levels in children with complicated convulsions compared to those having simple convulsions have also been reported.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6,12 However, studies have been reported in contrast to this evidence, 15,16 and the role of relative hyponatremia instead of serum sodium levels in the predisposition of the child to simple febrile seizure has been speculated. 17,18 Lower levels of mean sodium levels have been reported in patients with repeat convulsions, which was comparable to our study. 6 Lower sodium levels in children with complicated convulsions compared to those having simple convulsions have also been reported.…”
Section: Discussionsupporting
confidence: 91%
“…6 , 12 However, studies have been reported in contrast to this evidence, 15 , 16 and the role of relative hyponatremia instead of serum sodium levels in the predisposition of the child to simple febrile seizure has been speculated. 17 , 18 …”
Section: Discussionmentioning
confidence: 99%